2017
DOI: 10.2134/itsrj2016.05.0417
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Zoysiagrass Genotypes on Rooting Capacity and Associated Performance during Drought

Abstract: Characterization of rooting capacity in the greenhouse is a routine screening procedure for assessing a plant's ability to cope with drought stress. However, an association between rooting capacity in the greenhouse and turf performance in the field during drought is not always found. The objectives of the study were (i) to classify zoysiagrass (Zoysia spp.) rooting characteristics under well‐watered conditions in the greenhouse, (ii) to compare zoysiagrass performance under drought conditions in the field, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…Previous research found differences in rooting characteristics among 25 zoysiagrasses, with root depth and numbers of roots deeper in the soil found to correlate significantly with drought performance based on percentage green cover (Marcum et al, 1995). Another study that also looked at rooting characteristic of wellwatered plants in greenhouse conditions, and then compared those results to field conditions, also found that RLD and root biomass from the middle and lower soil profile were positive predictors of drought performance, whereas shallow-rooted plants that had much of their roots in the upper soil profile correlated negatively with drought performance (Christensen et al, 2017). Although in the current study no single root trait accounted for drought avoidance, differences in rooting characteristics can help explain some of the results of individual genotypes, as well as account for differences in transpiration.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous research found differences in rooting characteristics among 25 zoysiagrasses, with root depth and numbers of roots deeper in the soil found to correlate significantly with drought performance based on percentage green cover (Marcum et al, 1995). Another study that also looked at rooting characteristic of wellwatered plants in greenhouse conditions, and then compared those results to field conditions, also found that RLD and root biomass from the middle and lower soil profile were positive predictors of drought performance, whereas shallow-rooted plants that had much of their roots in the upper soil profile correlated negatively with drought performance (Christensen et al, 2017). Although in the current study no single root trait accounted for drought avoidance, differences in rooting characteristics can help explain some of the results of individual genotypes, as well as account for differences in transpiration.…”
Section: Discussionmentioning
confidence: 96%
“…The goal of our experiment was to measure drought avoidance traits in a collection of zoysiagrasses subjected to water-limited conditions. Several studies have examined rooting traits (Carrow, 1996b;Christensen et al, 2017;Fuentealba et al, 2015;Marcum et al, 1995) and supplemental water requirements (Qian and Engelke, 1999;Wherley et al, 2014;White et al, 1993) as they relate to drought performance in zoysiagrasses, but there is a lack of research that looks at belowground root traits and aboveground drought avoidance traits (such as g S ) integrated in a single study. We hypothesize that zoysiagrass genotypes that can use both extensive rooting and reduced transpiration through regulation of stomatal aperture will display the best drought performance.…”
mentioning
confidence: 99%
“…Grasses with a more uniform root distribution generally have better turf performance (Christensen et al 2017;Fuentealba et al, 2015). Christensen et al (2017) found that under dry soil conditions, zoysiagrass genotypes with shallower root distribution had lower turf performance, showing a negative correlation between the fraction of surface root length (i.e. root length from surface upper depth divided by total root length) and drought avoidance.…”
Section: Discussionmentioning
confidence: 99%
“…Grasses with a more uniform root distribution generally have better turf performance (Christensen et al. 2017; Fuentealba et al., 2015). Christensen et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation